Classification of conventional grain warehouses based on their a constructional and functional characteristics - Serôdio, Rogério dos Santos; Prado, Edison Pires do; Rihan, Eduardo Maron (Pesquisa Agropecuaria Brasileira, 2014)
Static classification of conventional warehouses for grain is defined as that which is based upon the structural and functional characteristics of these buildings. This classification falls under a more complex, prophylactic and sanitary classification (varying with time). The interest in such a classification is the contribution it gives to the study and surveying of grain storage conditions. Other classifications are mentioned and a complete view of a sanitary or dynamic classification is presented before a static classification of cacao farm warebouses is developed. This static classification is based on data of a regional survey, and a criterium of values, which yielded a definition of classes, was established.